Meta analyzing the ease of use of e-modules in learning - Putra, Yogi Irdes; Fadli, Radinal; Dahry, Sundahry (Universitas Negeri Yogyakarta, 2023)
Technological innovation in education is necessary to increase the quality of learning by utilizing specialized media. One of the efforts made by educators is to use e-modules in learning. E-modules are digital media containing text, video, audio, and animation, which are combined according to the learning needs of students/students. This research was conducted to describe the practicality of using e-modules for teachers/lecturers and students/students. In this study, ten articles were sampled regarding the use of e-modules. Based on the research results, it is known that the average practical value of using e-modules for teachers is 90.63 in the convenient category, while the average practical value of students is 87.09 in the applicable category. Based on the results of a review of the use of the developed e-module, it is included in the practical category so that the e-module can be used in learning activities.